Diversification of rice (Oryza sativa)-based cropping system of Varanasi for enhanced productivity and employment generation - SAHA, PRIYANKA; BOHRA, JITENDRA SINGH; NAYAK, HARSITA; SINGH, TEJBAL; BARMAN, ANAMIKA (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during 2019–20 with an objective to study the effect of diversification of rice- wheat cropping system with different fodder, legume and high value crops for enhanced productivity and employment generation under irrigated ecosystem. The rice equivalent yield was maximum with sudan fodder (4412 kg/ha), capsicum (8371 kg/ha) and lady’s finger (6519 kg/ ha) for rainy (kharif), winter (rabi) and summer season, respectively. However, high value rice-potato-lady’s finger recorded significantly higher system productivity and was comparable to high value rice-capsicum-vegetable cowpea sequence. Cropping sequences containing more than one crop gave better land use efficiency and more employment generation opportunities by engaging more farm labours. Hence, both the sequences, S9 and S10 recorded higher land use efficiency and labour engagement over other crop sequences thus leading to better employment generation.